2019
DOI: 10.36685/phi.v5i2.243
|View full text |Cite
|
Sign up to set email alerts
|

Low Birth Weight Is a Risk Factor of Malnutrition in Children Under Five Years Old in Coastal Areas

Abstract: Background: Malnutrition is a public health problem, especially in developing countries. Malnutrition of children can affect brain development during growth and increase morbidity and mortality. Low birth weight (LBW) plays an important role in child morbidity and mortality. The prevalence of malnutrition in children under five years old and LBW in Indonesia are still high.Objective: This study aimed to assess the risk of LBW on the incidence of malnutrition in children under five years old in coastal areas.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The study suggests that the lack of fiber intake in CHD patients is due to their eating habits, as they consume less food that is a source of fiber, especially water-soluble fiber. The study recommends a diet that includes soluble fiber, which helps lower cholesterol levels, and insoluble fiber, which is important for normal stomach function (Arora, 2008;Saimin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The study suggests that the lack of fiber intake in CHD patients is due to their eating habits, as they consume less food that is a source of fiber, especially water-soluble fiber. The study recommends a diet that includes soluble fiber, which helps lower cholesterol levels, and insoluble fiber, which is important for normal stomach function (Arora, 2008;Saimin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Mothers who experience SEZ have a greater potential to give birth to LBW babies [18] Based on the sub-districts, it is known that the low birth babies in 2020 is mostly happen in Tumbu-Tumbu Jaya sub-district, which is a coastal area. This is related to the fact that most pregnant women in coastal areas have a normal BMI before pregnancy which indicating the availability of nutritional reserves during later pregnancy to support her pregnancy [19]. This is likely cause less weight gain during pregnancy which can give birth to babies with low birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that malnutrition is much higher in children with LBW than in children without LBW [ 29 – 31 ]. According to the World Health Organisation (WHO), low birth weight babies are those who are born weighing less than 2500g [ 32 ].…”
Section: Introductionmentioning
confidence: 99%